2007
DOI: 10.1103/physrevd.76.084030
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-black holes: Definition and general properties

Abstract: Objects that are on the verge of being extremal black holes but actually are distinct in many ways are called quasi-black holes. Quasi-black holes are defined here and treated in a unified way through the displaying of their properties. The main ones are (i) there are infinite redshift whole regions, (ii) the spacetimes exhibit degenerate, almost singular, features but their curvature invariants remain perfectly regular everywhere, (iii) in the limit under discussion, outer and inner regions become mutually im… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(142 citation statements)
references
References 37 publications
6
136
0
Order By: Relevance
“…Such a kind of behavior is called naked behavior, and many instances of it have been found [9,10,11,12,13,14,15,16]. Another example is with quasi-black holes [5]. One of the features typical of quasi-black holes, consists in precisely showing naked behavior on and beyond the quasihorizon surface.…”
Section: Equations and Setup For Mimickersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a kind of behavior is called naked behavior, and many instances of it have been found [9,10,11,12,13,14,15,16]. Another example is with quasi-black holes [5]. One of the features typical of quasi-black holes, consists in precisely showing naked behavior on and beyond the quasihorizon surface.…”
Section: Equations and Setup For Mimickersmentioning
confidence: 99%
“…Within the uncharged or charged but non-extremal one can invoke as black hole mimickers, non-extremal ε-wormholes on the threshold of the formation of an event horizon, some of which are called black foils [2] (see [3] for the construction with other purposes of ε-wormholes, which actually can also act as mimickers), and gravastars [4]. Within the extremal charged class one can invoke extremal ε-wormholes on the threshold of the formation of an event horizon, quasi-black holes [5] (see also [6]), and wormholes on the basis of quasi-black holes from Bonnor stars, to name a few. We want to elucidate, whether or not the objects belonging to these two classes remain regular in the near-horizon limit.…”
Section: Introductionmentioning
confidence: 99%
“…Although to external observers the system looks like an extremal black hole, its internal properties are very different from what one could expect in the case of a standard black hole. These properties, along similar ones of gravitational magnetic monopoles and glued vacuum solutions with shells, have been analyzed in [16,17]. In [18] other attributes of these systems were explored.…”
Section: Bonnor Stars: Junction Of Dust With Vacuum Majumdar-papapetrmentioning
confidence: 99%
“…Later, it was shown that the hoop should be reduced for extremal charged matter to ∼ 2πGM [9,10]. However, it seems that systems like Bonnor stars violate it, since no black hole forms ever, only a quasi-black hole [16,17]. (v) A pertinent question, specially related to stars, is whether they can form from gravitational collapse or not.…”
Section: Further Connectionsmentioning
confidence: 99%
See 1 more Smart Citation